Plasmablastic lymphoma of nose and para-nasal sinuses in an immunocompetent patient - Chakravati, Arunabha; Mojahid, Moazzam; Nair, Rohini R.; Agarwal, Shilpi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Plasmablastic lymphoma (PbL) is a rare and aggressive neoplasm with heterogeneous clinical, histological and genetic features. It has been reported in both immuno-compromised and immuno-competent patients and commonly presents in the extra-nodal regions, but it is more heterogeneous in immuno-competent patients. Its clinical course is aggressive with early dissemination and poor response to therapy. A 61 year old male presented with left sided nasal bleeding and nasal obstruction for last 6 months, snoring and disturbed sleep for last 2 months. On examination, there was fullness over left side of nose and obliteration of left naso-facial groove. A mass lesion was seen in the left nasal cavity on endoscopy. There was bulge in the soft palate and the mass extended into the oropharynx. CECT showed a locally aggressive sino-nasal mass. Histopathology and immuno-histo-chemistry (IHC) of the biopsy were suggestive of plasmablastic lymphoma. A debulking surgery was done to relieve his obstructive symptoms. The patient received 3 cycles of EPOCH chemotherapy and radiotherapy to local site. At 9 months of follow up he presented with recurrence of the mass. Plasmablastic lymphoma presents in patients other than those with HIV. Awareness about its unique characteristics is crucial for establishing a correct diagnosis. Currently available treatments are ineffective in achieving long term remission and prognosis remains unfavourable with high incidence of recurrence